Posterior uterine wall rupture in an unscarred uterus in a term pregnancy; a case report - Mesfin Ayalew Tsegaye; Alemayehu Nigusssie Adugna; Rebecca Haile Tesfay; Elias Gashaw Endegnanew; Kidist Nega Aragaw (Elsevier, 2024)
Uterine rupture is a catastrophic separation of the uterine walls due to several risk factors. It is a common complication of scarred uterus during labor and delivery. Early detection is associated with better maternal and fetal outcomes. Due to nonspecific presentation, a high level of suspicion especially on pregnancies with risk factors could help pick uterine rupture early. This report presents a gravida 11 para 10 mother who presented with vaginal bleeding and severe abdominal pain after laboring for 24 h at home. Intra-op findings were approximately 1000 ml of hemoperitoneum with the fetus and the placenta floating on the peritoneal cavity and a 13 cm posterior uterine rupture with vaginal extension. A subtotal hysterectomy and left salpingo-oophorectomy were done She was discharged well after several blood transfusions. The objective is to present a rare case of posterior wall uterine rupture and to emphasize the importance of early detection of posterior wall uterine ruptures.